Constructing SAMs from the SNA - Santos, Susana (2011)
A SAM (Social Accounting Matrix) approach can be an important aid for the modelling of economic policy and a valuable support in the decision-making process, since it provides a description of the measurable part of a society’s activity. Richard Stone made the first and most fundamental contribution to the System of National Accounts (SNA), implemented by the United Nations. Benefiting from successive improved versions since 1953, this system has defined the rules for using the above-mentioned measurement tool. In turn, statistical offices have considered these rules and adapted them to their specific realities, thus defining their own systems, which they have then used as guidelines for measuring the activity of their countries or groups of countries. With these successive improvements, as embodied in the SNA’s latest version from 2008, the description of the activity of a society, its specific characteristics and the problems that it faces have become more realistic. Therefore, the use of the SNA in a SAM-based approach will certainly contribute towards a better modelling of economic policy. Numerical and algebraic versions of the SAM will be examined, with special attention being paid to the former and to the method of its construction from the SNA. Its basic structure and its consistency within the whole system will be studied, as well as any possible disaggregations, extensions, aggregates, indicators, and balances that can be calculated. Other aspects beyond that basic structure will also be examined. An application will be made to Portugal.